2014
DOI: 10.1177/0266242614550322
|View full text |Cite
|
Sign up to set email alerts
|

Are pure or hybrid strategies right for new ventures in transition economies?

Abstract: This article examines the role of strategic intensity or commitment to a chosen course of action, and the impact of pure versus hybrid competitive strategies on competitive performance in transition economies, using survey data ( N = 333) from Bulgaria. We find that strategic intensity is positively related to performance; firms that deviate from pure cost leadership or differentiation and achieve a balance on both dimensions report superior performance. In a post hoc analysis of our data, we find preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 83 publications
1
27
0
Order By: Relevance
“…Overall model result show that 13% of the variation in wealth created was due to the strategy adopted by the SMEs. This result corroborate the finding of Maney, Manoloya, Harkins, and Gyoshey (2014) that strategic intensity is positively related to performance; firms that deviate from pure cost leadership or differentiation and try to achieve a balance on both dimensions. Such balance is observed in the r values for product differentiation (r=0.15**) and cost parity (r=0.01**).…”
Section: Strategysupporting
confidence: 89%
See 2 more Smart Citations
“…Overall model result show that 13% of the variation in wealth created was due to the strategy adopted by the SMEs. This result corroborate the finding of Maney, Manoloya, Harkins, and Gyoshey (2014) that strategic intensity is positively related to performance; firms that deviate from pure cost leadership or differentiation and try to achieve a balance on both dimensions. Such balance is observed in the r values for product differentiation (r=0.15**) and cost parity (r=0.01**).…”
Section: Strategysupporting
confidence: 89%
“…For example: Escriba-Esteve, Sanchez-Peinado and Sanchez-Peinado (2008) establish positive and significant relationship between SMEs' strategic orientation and performance; Maney, Manoloya, Harkins, and Gyoshey (2014) find that strategic intensity is positively related with performance; firms that deviate from pure cost leadership or differentiation and achieve a balance on both dimensions report superior performance; they further report that strategic intensity may act as a mediator of the relationship between strategic type and performance. Asikhia and Jansen van Rensburg (2015) identify the main SMEs' strategies as; product differentiation, strategic entrepreneurship, niche strategy, cost parity, opportunity seeking abilities, advantage seeking abilities and growth orientation.…”
Section: Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Beal and Yasai-Ardekani (2000), consistently with Claver-Cortes et al (2012), proposed that hybrid strategies may yield multiple sources of advantage over rival firms, and so allow achievement of higher performance and this makes it difficult to imitate hybrid strategies. In conclusion, the firms' ability to use hybrid strategy may be more important than maintaining competitive advantage (Carter, Stearns & Reynolds, 1994;Kim & Choi, 1994;Parnell & Hershey, 2005 Leitner & Güldenberg, 2010;Hodgkinson, 2013;Parnell, 2013;Manev, Manolova, Harkins & Gyoshev, 2014;Salavou, 2015).…”
Section: Discussion On Pure or Hybrid Strategymentioning
confidence: 99%
“…While some studies revealed that pure strategies improved performance (Ebben & Johnson, 2005;Lechner, Gudmundsson & Vidar, 2014;Hansen, Nybakk & Panwar, 2015), others suggested that different generic strategies were linked to different aspects of performance (Chandler & Hanks, 1994;Baum, Locke & Smith, 2001). There is another group of studies, which indicated that hybrid strategies, combining elements of both generic competitive strategies, simultaneously lead to better performance (Carter, Stearns & Reynolds, 1994;Kim & Choi, 1994;Acquaah & Yasai-Ardekani, 2008; Pertusa-Ortega, Molina-Azorí n & Claver-Corté s, 2009; Leitner & Güldenberg, 2010;Hodgkinson, 2013;Parnell, 2013;Manev, Manolova, Harkins & Gyoshev, 2014;Salavou, 2015). Hybrid strategies involving high level of emphasis on both cost-leadership and differentiation strategies simultaneously should be distinguished from stuck in the middle strategy where a firm fails to successfully pursue both cost-leadership and differentiation strategies (Acquaah & Yasai-Ardekani, 2008).…”
Section: Introductionmentioning
confidence: 99%